THE RELATIONSHIP BETWEEN RELIGIOUS EDUCATION AND RELIGIOUS DELUSIONS IN PATIENTS WITH SCHIZOPHRENIA: A CROSS-SECTIONAL STUDY - Siti Nurafifah Qarimah; Mohd. Rizal Fahmi Adha; Cut Aja Nuraskin (Getsempena Health Science Journal, 2025)
The prevalence of religious-themed delusional thinking among individuals with schizophrenia varies significantly across different countries and cultural contexts. Despite the relevance of this phenomenon, in-depth studies focusing on religious delusions within Islamic contexts remain scarce. To gain a deeper understanding of psychotic symptoms involving religious content, this study investigates the potential relationship between religious education and the manifestation of religious delusions.This study aims to explore the association between religious education and the occurrence of religious delusions in patients diagnosed with schizophrenia. A quantitative, correlational research design was employed using a cross-sectional approach. A total of 127 participants were recruited through total sampling, all of whom met the established inclusion criteria. Data collection was conducted over a two-month period using structured interviews and five assessment tools: a sociodemographic questionnaire, the Scale for the Assessment of Positive Symptoms (SAPS), a Religious Delusion Algorithm, the Peters Delusions Inventory (PDI), and the Brown Assessment of Beliefs Scale (BABS). Data were analyzed through univariate, bivariate, and multivariate logistic regression analyses. The results indicate a significant relationship between religious education and the presence of religious delusions, as evidenced by the logistic regression analysis (OR = 30.85, 95% CI [6.027, 157.92]).Conclusion: This study concludes that there is a relationship between religious education and the occurrence of religious delusions in individuals with schizophrenia. These findings highlight the importance of considering a patient's religious background in the diagnostic and therapeutic approach to psychotic disorders involving religious content.